The Use of Total Reflection X-Ray Fluorescence in an Underwater Archaeology Case Study - Vázquez, Cristina (2010)
This paper demonstrates the applicability of total reflection x-ray fluorescence (TXrf) as a powerful analytical tool for discovering the composition of the liquid inside a bottle found in the hMs Swift, a British warship which sank off Patagonia in 1770. in order to characterize the contents of the bottle, a microsample was submitted for TXrf determination. The collected spectrum clearly showed the presence of chloride (cl) and mercury (hg) signals which were quantified using gallium (ga) as an internal standard. after quantification, results perfectly match mercurous chloride (hg2 cl2 ), a compound which has historically had several pharmacological applications.